A puzzle unravelled: pancytopenia and hepatosplenomegaly in juvenile autoimmune hypothyroidism - Nayak, Yankappa; Reddy, Mounika; Ghantasala, Manogna; Mundhe, Ragini; Samprathi, Madhusudan (International Journal of Contemporary Pediatrics, 2024)
Autoimmune thyroiditis is a common cause of hypothyroidism in adolescent females. While normocytic normochromic anemia is a recognized association with hypothyroidism, pancytopenia is seldom reported. This case report discusses a young adolescent girl with autoimmune hypothyroidism presenting with severe pancytopenia and hepatosplenomegaly. After extensive evaluation, hypoproliferative marrow with extramedullary hematopoiesis secondary to uncontrolled hypothyroidism was considered to be the most likely cause. Swift recovery following appropriate levothyroxine replacement further supports this hypothesis. Thus, hypothyroidism can be a potential cause of pancytopenia with hepatosplenomegaly. Early recognition and appropriate management can lead to prompt resolution and prevent unnecessary invasive procedures.